0910-F-021 effect of cutting speed and depth of cut on surface roughness of mild steel in turning operation - Thien, Shiela Nga Ting (2009)
In metal cutting and manufacturing industries, surface finish of a product is very crucial in determining the quality. Good surface finish not only assures quality, but also reduces manufacturing cost. Surface finish is important in terms of tolerances, it reduces assembly time and avoids the need for secondary operation, thus reduces operation time and leads to overall cost reduction. Besides, good-quality turned surface is significant in improving fatigue strength, corrosion resistance, and creep life. In this research, the main objective is to study the effect of cutting speed and depth of cut on surface roughness of mild steel in turning operation. And MINITAB 15 software was used to predict the surface roughness. Both predicted and experimental results were then compared. Different cutting parameters have different influential on the surface finish. In the experiment conducted in this research, 3 cutting speed and 5 depth of cut were used. Using Taguchi Orthogonal Array as design of experiment, the total set of experiments carried out is 15 sets. At first, the mild steel was undergone chemical composition test using Arc Spectrometer, and was decide that it might be of grade AISI 1022. The cutting speed and depth of cut were decide using the suitable range recommended; which were 490rpm, 810rpm and 1400rpm for cutting speed, 0.1mm, 0.2mm, 0.3mm, 0.4mm, and 0.5mm for depth of cut. The specimen was turned under different level of parameters and was measured the surface roughness using a Perthometer. From the result, it is concluded that higher cutting speed or lower depth of cut produce better surface finish. The optimum cutting speed and depth of cut in this case were 1400rpm and 0.1mm, which produced average surface roughness 4.695μm. Response Surface Method (RSM) was used to predict the surface roughness. And from the result generated, the correlation for surface roughness with the cutting parameters satisfies a reasonable degree of approximation. Both cutting speed and depth of cut are a significant parameter in influencing the surface roughness.